Paediatric preoperative sedation practices in tertiary maternity and children's hospitals in China: a questionnaire survey - Bo Li; Huiyan Hou; Jie Bai; Mazhong Zhang; Shengde Li; Jijian Zheng (BMC, 2021)
Abstract Background Preoperative anxiety is a common problem in the paediatric population, and several studies have reported that it is related to adverse events such as emergence delirium and postoperative psychological and behavioural changes. In recent years, increasing attention has been paid to paediatric preoperative anxiety in China. A variety of strategies, including sedatives, parental presence, and audio-visual interventions, have been used to relieve paediatric preoperative anxiety, but there is no well-recognised procedure for paediatric preoperative sedation. Therefore, this study aimed to investigate current paediatric preoperative sedation practices in tertiary children's hospitals in China. Methods All tertiary maternity and children's hospitals registered with the National Health Commission of the People's Republic of China were invited to participate in an electronic survey, which included information on the preoperative sedation caseload, sites where preoperative sedation was performed, preoperative sedation methods used in different age groups, choice of sedatives, contraindications for premedication, staff structure for sedative administration and monitoring, and patient-monitoring practices. Results All 81 hospitals participating in our study completed the survey, and 38 hospitals (46.9 %) provided their preoperative sedation protocols. Twenty-four hospitals performed fewer than 5,000 preoperative sedation cases annually, and 9 hospitals performed more than 10,000 cases annually. Preoperative sedation was performed in preoperative preparation areas, preoperative holding areas, and operation rooms in 47.4 %, 26.3 %, and 13.2 % of hospitals, respectively. Sedatives were the most used interventions for paediatric preoperative sedation in all age groups, and the most widely used sedatives were propofol (intravenous) and dexmedetomidine (intranasal). The most common contraindications were American Society of Anesthesiologists class ≥ 3, emergency operation, and airway infection within 2 weeks. Sedatives were administered mainly by anaesthesiologists (63.2 %), and children were monitored mainly by anaesthesiologists (44.7 %) and nurses (39.5 %) after administration. Pulse oximetry was the most widely used monitoring device. Conclusions Fewer than half of the tertiary maternity and children's hospitals in China provide paediatric preoperative sedation service, and the service practices vary widely. Further improvements are required to ensure the quality of paediatric preoperative sedation services and establish standard operating procedures.